DEVELOPMENT OF INTERCULTURAL COMMUNICATION SKILLS IN ESP LAW COURSE (Education in the 21st Century, 2023)
This paper targets the vital issues of forming intercultural competence in the legally oriented English course. Nonnative law students whose first or native language is Armenian often find it challenging to communicate with their native English-speaking colleagues on legal topics. So, it is essential to develop the methodological system of forming intercultural and communicative skills in teaching legally oriented sublanguage based on the principles of the communicative approach, ESP, and intercultural competence. However,the solution of promoting intercultural communication skills on the general scientific, colloquial, and professional levels is multilayered, covering:pedagogical conditions of learning English legal sublanguage; 2. The availability of modern technologies, 3. workable methods of teaching foreign languages, 4. Cognitive and professional needs of future lawyers/ to learn professional English for occupational purposes- to join the job market, 5. the positive experience gained in recent years in countries with great methodological traditions.The aim of the research is to state and substantiate the necessity of developing intercultural communicative skills in legal English courses to raise professional legal English competency.The novelty of the research is to develop the methodological system of forming intercultural and communicative skills in teaching legally oriented sublanguage based on the communicative, conceptual approaches, ESP, and intercultural competence principles.The conclusion: The conducted experiment confirmed that the applied materials, teaching strategies, and communicative methods, and conceptual approaches might be a better way to teach legal English while developing intercultural and communicative competencies, as well as raising common and legal culture awareness.
Keywords: Legal English; culture; concepts; communicative skill; intercultural; methodology